Maine’s Dubious Odyssey into the Funding of Local Government - Mills, Peter (Maine Policy Review, 1999)
Despite recent reforms to Maine’s school funding, State Senator Peter Mills argues that the formula will not be truly “fixed” until the state addresses the municipal side of property tax inequities. To that end, he prescribes some tough medicine for Maine policymakers to relieve the disproportionate tax burden on the state’s service center communities. Among other things, he suggests we consider repealing some of the exemptions that exclude a quarter of all property from taxation; permitting service centers to adopt local option taxes; and injecting the state’s limited revenue sharing funds into just those municipalities with intolerable tax burdens that remain unmanageable through local resources. Moreover, Mills asserts that the state “cannot relieve inequity by trying to carpet bomb the property tax.” He calls for an end to expensive and unfocused measures that sprinkle the state’s revenue too broadly. With income tax rates among the highest in the nation (and a sales tax soon to be reduced), Mills argues that Maine’s failure to address property tax inequities squanders the state’s limited resources and places the state’s future economic competitiveness in jeopardy.
Keywords: Maine local government funding; Maine property tax; state-local revenue sharing